Prevalence, awareness and control of diabetes in Russia: The Ural Eye and Medical Study on adults aged 40+ years - Bikbov, Mukharram M.; Fayzrakhmanov, Rinat R.; Kazakbaeva, Gyulli M.; Zainullin, Rinat M.; Arslangareeva, Inga I.; Gilmanshin, Timur R.; Salavatova, Venera F.; Nikitin, Nikolai A.; Mukhamadieva, Svetlana R.; Yakupova, Dilya F.; Khikmatullin, Renat I.; Zaynetdinov, Artur F.; et al. (PloS one, 2019)
Non-communicable chronic diseases have become the leading causes of mortality and disease burden worldwide. With information about the frequency of diabetes as a major non-communicable chronic disease in Russia being scarce, we assessed the prevalence of diabetes and its associated factors in a rural and urban population in Russia. The Ural Eye and Medical Study is a population-based study in the city of Ufa/Russia and in villages in a distance of 65 km from Ufa. Inclusion criterion was an age of 40+ years. All study participants underwent a standardized interview and a detailed general examination. Diabetes mellitus was defined by a plasma glucose concentration ≥7.0 mmol/L or self-reported history of physician diagnosis of diabetes. Out of a population of 7328 eligible individuals, 5899 individuals (2580 (43.7%) men) (participation rate:80.5%) participated (mean age:59.0±10.7 years (range:40-94 years)). Diabetes mellitus was present in 687 individuals (11.7%;95% confidence interval (CI):11.9,12.5). Awareness rate of having diabetes was 500/687 (72.8%;95%CI:69.0,76.0), with mean known duration of diabetes of 10.0±9.4 years. Known type 1 diabetes was present in 44 subjects and known type 2 diabetes in 358 subjects. Prevalence of undiagnosed diabetes was 3.2% (95%CI:2.7,3.6) in the study population. Among patients with diabetes, 59.1% (95%CI:55.4,62.8) received treatment for diabetes, among whom 237 (58.5%;95%CI:53.7,63.3) individuals had adequate glycemic control. In multivariable analysis, higher prevalence of diabetes mellitus was associated with older age (P<0.001; odds ratio (OR):1.03;95%CI:1.01,1.04), higher body mass index (P<0.001;OR:1.07;95%CI:1.04,1.10), lower prevalence of vigorous daily work (P = 0.002;OR0.68;95%CI:0.53,0.87), positive history of arterial hypertension (P = 0.03;OR:1.40;95%CI:1.03,1.89) and cardiovascular diseases (P = 0.001;OR:1.60;95%CI:1.21,2.13) including heart attacks (P = 0.01;OR:1.80;95%CI:1.15,2.81), higher serum concentration of triglycerides (P<0.001;OR:1.51;95%CI:1.30,1.75), higher systolic blood pressure (P = 0.01;OR:1.01;95%CI:1.01,1.02), higher number of meals taken daily (P<0.001;OR:1.46;95%CI:1.25,1.69), and non-Muslim religion (P = 0.02;OR:0.73;95%CI:0.56,0.94). In this ethnically mixed, urban and rural Russian population aged 40+ years, the awareness rate of diabetes (72.8%) was relatively high, while the diabetes prevalence (11.7%) was comparable with that of other countries such as China and the USA. Factors associated with higher diabetes prevalence were similar in Russia and these other countries and included older age, higher body mass index and higher serum concentration of triglycerides, lower prevalence of vigorous daily work, arterial hypertension and cardiovascular diseases.